Combined use of in-reservoir geological records for oil-reservoir destruction identification: A case study in the Jingbian area (Ordos Basin, China) - Yang, Zeguang; Wang, Aiguo; Meng, Pengyun; Chen, Min; Guo, Kai; Zhu, Nan (Frontiers in Earth Science, 2023)
Rapid identification of reservoir destruction is critical to avoid exploration failure. More indicators of reservoir destruction are urgently needed to be developed besides the evaluation methods of trap effectiveness based on structural analysis,. Here, we provide a case study in the Ordos Basin to show that the combined use of in-reservoir geological records is a robust tool to rapidly identify oil-reservoir destruction. The sandstones within the Yanchang Formation in the oil-depleted Jingbian area were investigated by petrological and geochemical analysis. The results show that (1) the oils with increased density and viscosity occur in the low permeability sandstones, whereas the high permeability sandstones were occupied by water, (2) abundant solid bitumen occur in the intergranular pores, (3) the n-alkanes with carbon numbers less than 19 are significantly lost from the original oils, and (4) the majority of paleo oil layers have evolved into present water layers. All these in-reservoir physicochemical signatures unravel the same geological event (i.e., oil-reservoir destruction) in the Jingbian area. This oil-reservoir destruction was likely caused by the uplift-induced erosion and the fault activities after oil accumulation during the Late Early Cretaceous.